Leveraging Agriculture for Nutrition in East Africa (LANEA) Country Report – Ethiopia - Beyero, Mesfin; Hodge, Judith; Lewis, Amanda (Food and Agriculture Organization of the United Nations, 2015)
LANEA (Leveraging Agriculture for Nutrition in East Africa) is an IFPRI/FAO research initiative carried out in Ethiopia, Uganda and Kenya to investigate opportunities and challenges related to scaling up impact on nutrition through the food and agriculture sector. The LANEA Ethiopia study highlights stakeholder perspectives regarding how agriculture can be leveraged to achieve improvements in nutrition